Grain boundary diffusion and segregation of 57Co in high-purity copper: Radiotracer measurements in B- and C-type diffusion regimes. (1st April 2017) - Gaertner, Daniel; Wilde, Gerhard; Divinski, Sergiy V.
Abstract: Grain boundary diffusion of 57 Co in high-purity polycrystalline copper is investigated using the radiotracer technique in Harrison's B- (850–1150 K) and C-type (550–950 K) kinetic regimes. The triple product P  =  s · δ · D gb ( s is the segregation factor and δ the grain boundary width) and the grain boundary diffusion coefficient D gb of Co in Cu are determined to obey the Arrhenius laws with the activation enthalpies of Q gb  = 66.2 kJ/mol and H gb  = 100.9 kJ/mol, respectively. Using the experimental estimate of δ, δ ≅ 0.5  nm, Co is found to segregate strongly at Cu grain boundaries and the corresponding segregation factor follows an Arrhenius dependence with the segregation enthalpy of H s  = −34.7 kJ/mol. Co-diffusion experiments with the 57 Co and 110m Ag isotopes support a 'sub-interface'-type of grain boundary segregation of Co in Cu. Graphical abstract: Image 1